F-1,000,000,000,000 [compact disc] - Malone, Post, 1995- (Mercury/Republic, 2024)
Post Malone releases his first-ever full-length country album. Paving the way was the first single "I Had Some Help" with Morgan Wallen, which continues to dominate the charts and the conversation. Post also released "Pour Me A Drink" featuring Blake Shelton. The album arrives on the heels of Post's landmark set at Stagecoach Festival 2024 in Indio, CA with a lineup of country covers and welcomed superstar guests.